2019
DOI: 10.1111/jcmm.14578
|View full text |Cite
|
Sign up to set email alerts
|

PLCA8 suppresses breast cancer apoptosis by activating the PI3k/AKT/NF‐κB pathway

Abstract: The cysteine‐rich lysosomal protein placenta‐specific 8 (PLAC8), also called onzin, has been shown to be involved in many types of cancers, and its role is highly dependent on cellular and physiological contexts. However, the precise function of PLAC8 in breast cancer (BC) progression remains unclear. In this study, we investigated both the clinical significance and biological functions of PLAC8 in BC progression. First, high PLAC8 expression was observed in primary BC tissues compared with adjacent normal tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 41 publications
2
28
0
Order By: Relevance
“…PLAC8 has been described as a tumor suppressor and a tumor promoter in different types of cancer. For example, PLAC8 overexpression promotes the tumorigenic transformation in clear-cell renal-cell carcinoma, lung cancer, colon cancer and breast cancer, but it also suppresses the proliferation of hepatocellular carcinoma cells (12)(13)(14)(15)(16)(17). In accordance with the latter finding, the present study identified that PLAC8 expression was significantly lower in OSCC cell lines compared with human oral epithelial cells.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…PLAC8 has been described as a tumor suppressor and a tumor promoter in different types of cancer. For example, PLAC8 overexpression promotes the tumorigenic transformation in clear-cell renal-cell carcinoma, lung cancer, colon cancer and breast cancer, but it also suppresses the proliferation of hepatocellular carcinoma cells (12)(13)(14)(15)(16)(17). In accordance with the latter finding, the present study identified that PLAC8 expression was significantly lower in OSCC cell lines compared with human oral epithelial cells.…”
Section: Discussionsupporting
confidence: 88%
“…PLAC8 has been demonstrated to participate in immunity, adipocyte differentiation and embryo development (8)(9)(10). Previous studies have revealed that PLAC8 is closely associated with the proliferation, apoptosis and autophagy of tumor cells (11)(12)(13)(14). Some studies have reported that high PLAC8 expression is positively associated with progression of malignancy and that it promotes the proliferation of cancer cells in the colon and lungs, as well as in renal cell carcinoma (12,15,16).…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers showed that endogenous PLAC8 promoted cell proliferation and tumor formation in lung cancer (23). PLAC8 could also promote proliferation and inhibit apoptosis in breast cancer cells by activating the PI3K/AKT/NF-κB pathway (24). Interestingly, PLAC8 can exert different biological effects depending on the cell environment (25,26) so that HCC patients with a high level of PLAC8 had a high-risk score and bad prognosis in our risk model.…”
Section: Discussionmentioning
confidence: 91%
“…We also compared the WT and KO effector CD8 T cells based on their expression of surface markers IL-7Rα and KLRG1 which are indicative of effector CD8 T cell fate, however there were no differences in the expression of these surface markers, suggesting that Plac8 does not impact CD8 T cell differentiation pathways during influenza infection (S4C and S4D Fig). An alternate hypothesis is that Plac8 may promote CD8 T cell survival after IAV infection because it has been shown to promote cancer cell survival by limiting apoptosis [35,36]. Because apoptotic cells are rapidly scavenged in vivo by phagocytes, quantifying apoptosis in vivo remains challenging [37].…”
Section: Discussionmentioning
confidence: 99%